2013
DOI: 10.1111/nph.12382
|View full text |Cite
|
Sign up to set email alerts
|

Woody clockworks: circadian regulation of night‐time water use in Eucalyptus globulus

Abstract: SummaryThe role of the circadian clock in controlling the metabolism of entire trees has seldom been considered. We tested whether the clock influences nocturnal whole-tree water use.Whole-tree chambers allowed the control of environmental variables (temperature, relative humidity). Night-time stomatal conductance (g s ) and sap flow (Q) were monitored in 6-to 8-m-tall Eucalyptus globulus trees during nights when environmental variables were kept constant, and also when conditions varied with time. Artificial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
43
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 34 publications
1
43
0
Order By: Relevance
“…Strong evidence for endogenous regulation of g dark was reported by Resco de Dios et al . (), who showed that g dark fluctuated throughout the night, despite environmental conditions being held constant in whole‐tree chambers. In addition, g dark can show a clear response to VPD (Barbour & Buckley, ) during night‐time conditions.…”
Section: Use Of Minimum Conductance In Modelsmentioning
confidence: 99%
“…Strong evidence for endogenous regulation of g dark was reported by Resco de Dios et al . (), who showed that g dark fluctuated throughout the night, despite environmental conditions being held constant in whole‐tree chambers. In addition, g dark can show a clear response to VPD (Barbour & Buckley, ) during night‐time conditions.…”
Section: Use Of Minimum Conductance In Modelsmentioning
confidence: 99%
“…This nocturnal increase in g s may be attributed to the circadian clock when variation in the environmental drivers of g s is negligible (a "constant environment"). 8 However, with the exception of some overcast nights, temperature tends to decrease while relative humidity tends to increase during the night, which leads to a decrease in vapor pressure deficit (VPD). In those species where nocturnal g s shows a negative response to VPD, 9 the nocturnal increase in g s may be attributed to a combination of endogenous controls and of direct physiological responses to the environment.…”
Section: On the Persistence Of Memorymentioning
confidence: 99%
“…A major potential hindrance for modelling nocturnal transpiration is that different day- vs -night stomatal behaviours have been suggested, which would imply that applying models based on daytime parameterizations to nocturnal time periods would be problematic5. For instance, night-time stomatal conductance either does not respond to, or responds positively to, vapour pressure deficit in some species, contrary to the daytime trend419. Moreover, stomata tend to show higher conductance later than earlier in the night for a given level of vapour pressure deficit20 which would indicate that, in addition to direct responses to environmental variation, endogenous processes also affect nocturnal stomatal conductance.…”
mentioning
confidence: 99%
“…Endogenous regulation has often been attributed to the circadian clock419 but, to show circadian regulation, one would need to experimentally maintain constant environmental conditions under prolonged (>24 h) darkness. As far as we are aware, this has only been done by one study23 so far and under CO 2 -free air, which potentially affected stomatal behaviour.…”
mentioning
confidence: 99%